Fabrication of graphene oxide and graphene-oxide/peptide biofilms : characterization, cell viability and differentiation potential of Wharton's jelly mesenchymal stem cells - Puah, Perng Yang (2018)
Human Wharton's jelly mesenchymal stem cells (WJ-MSCs) treatments are being tested clinically for a range of disorders. Surface modification techniques have been instrumental in the development of biomaterials that promote cellsurface interactions. In this study, the surface of graphene oxide (GO) was modified to promote the proliferation and differentiation of Wharton's jelly mesenchymal stem cells (WJ-MSCs). Synthesized GO was prepared through modified Hummers method, fabrication of GO film using drop-casting method and attachment of peptide to GO film through non-covalent approach, n-rc and electrostatic interactions. Synthesized GO were confirmed by UV-vis, XRD and FTIR. SEM and AFM images showed that synthesized GO has curled transparent thin film with thickness of 1.10 nm. Four peptide sequences, namely Pepl ("N"-YIGSRWYQNMIRIKVAV-"C''), Pep2 ("N"QHREDGSYIGSRIKVAV-" C''), Pep3 ("N"-WQPPRARIYIGSRIKVAV-"C") and Pep4 ("N"-DGEARGDSPKRSR-"C") were designed based short peptide sequences derived from extracellular matrix (ECM) adhesion peptides. AFM results revealed the thickness of GO biofilm (0.25 mg/ml) was 82.6 nm ± 10.4 nm, corresponding to 65 - 85 layers of single layer GO. The GO biofilm (0.25 mg/ml) treated with Pepl shows decrease in thickness as compared to non-treated GO film and the present of peptide bond in GO/Pep biofilm was confirmed by modified Lowry method. Furthermore, GO biofilms with concentration lower than 0.25 mg/ml were able to maintain the cell viability at day 5 as compared to glass coverslip. The WJ-MSCs were able to attach and growth on GO film. Increased of cell viability at day 6 was observed for all the GO/Pep biofilms as compared to GO biofilm. GO and GO/Pep biofilm allowed WJ-MSCs attachment, proliferation and increased in osteogenic differentiation capacity. Besides, the cell cultured on GO and GO/Pep biofilm able to maintain its undifferentiated stem cell characteristic. The data obtained here collectively demonstrates that the GO/Peptide biofilm assemble via noncovalent approach is a potential substrate for the adhesion, proliferation and enhance osteogenic differentiation of human WJ-MSCs. In conclusion, GO/Pep biofilms can be utilized for designing and manipulating biomaterials for stem cell, biological and tissue engineering applications.